2014
DOI: 10.1088/0953-8984/27/1/013002
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide: from fundamentals to applications

Abstract: In this review, we discuss the fundamental characterization of graphene oxide (GO) and its future application perspectives. Morphology is discussed through optical microscopy, fluorescence microscopy, scanning electron microscopy, and atomic force microscopy studies. Chemical, structural, and vibrational properties are discussed through x-ray photoemission spectroscopy and Raman spectroscopy studies. Two easy characterization strategies, based on the correlation between x-ray photoemission spectroscopy and con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
106
0
7

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 149 publications
(115 citation statements)
references
References 130 publications
2
106
0
7
Order By: Relevance
“…Structure and composition of GO is ill-defined and depends on the method of preparation. 13 In the nanoscale, it has been found that GO is heterogeneous material consisting of graphene-like and oxide-like regions. However, it is not clear if the GO produced by the two-photon oxidation is similar to GO produced by chemical methods.…”
mentioning
confidence: 99%
“…Structure and composition of GO is ill-defined and depends on the method of preparation. 13 In the nanoscale, it has been found that GO is heterogeneous material consisting of graphene-like and oxide-like regions. However, it is not clear if the GO produced by the two-photon oxidation is similar to GO produced by chemical methods.…”
mentioning
confidence: 99%
“…The chemical nature of the interaction with tectomers is, however, different for both carbon nanomaterials: while carboxylic groups in GO are only located at the periphery of the GO structure, epoxyand hydroxyl groups extensively functionalize the basal plane, [86][87][88] and are capable of hydrogen bonding formation with the amino terminal groups of tectomers. Actually, strong ionic hydrogen bonds can be formed if amino groups are protonated as N +__ H•••O.…”
Section: Go/tectomer Hybridsmentioning
confidence: 99%
“…Em seguida, adicionaram-se gradualmente 3,0 g de KMnO 4 . A mistura foi agitada durante 2 h e depois diluída com água destilada.…”
Section: Síntese Dos Ogsunclassified
“…4,5 Desde o estudo pioneiro de Brodie várias rotas químicas foram propostas para sintetizar o OG, como a sugerida por Staudenmaier, 40 anos após Brodie, e por Hummers e Offeman, um século após o primeiro relato.…”
Section: Introductionunclassified
See 1 more Smart Citation